Discharge Planning Terintegrasi Dalam Pelayanan Klien DM di Ruang Rawat Inap Penyakit Dalam RSUD Solok Tahun 2017 - Titin Sumarni; Yulastri Yulastri; Abdul Gafar (Poltekkes Kemenkes Padang, 2019)
Diabetes mellitus type 2 is cronic disease that needed long term treatment. So that is need Discharge Planning. The appliying of an integrated Discharge Planning will influence the a patient treatment when he / she comes back home. The purpose of this research results a Discharge Planning modul and analysis of the implementation influence of Discharge Planning modul toward a patient knowledge in DM matter. The research method uses quasi experiment with the design of after-before analysis with McNemar test. The sample used is purposive sampling with 39 samples, date collected uses questionare with interview, data is calcuted and analyzed. The research result shows that there is a significant difference in knowledge between bifor and after implementation of Discharge Planning module (p=0,010). Sugested for hospital managemen to made and implemented Discharge Planning module.